2022
DOI: 10.1088/1757-899x/1258/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn, Mg and heat treatment on Al base alloy on hardness using Taguchi Technique

Abstract: In the current investigation, effort has been made to develop the Al-Zinc-Mg alloy by changing weight percentage of Zn (5.1, 5.6 and 6.1) and weight percentage of Mg (2.1, 2.5 and 2.9) through liquid metallurgy process. Developed Al-Zn-Mg alloy is exposed to solutionzing treatment at 450°C for holding period of 3 hrs. followed by ageing at 180C for 3 hrs and then Retrogression Reageing (RRA) at 150C for a holding period of 3, 5 and 7 hrs. Then the modified Al-Zn-Mg cast alloys were cut and machined as per ASTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Table 1 illustrates that Al 7075-Sc contains 0.11% Sc in addition to 6.6% Zn, which is almost 1 percent higher than Al 7075 which has 5.62% Zn. The results of the study by Pruthvi and Shenoy [25] also indicated that the weight percentage of Zn has the most significant contribution to hardness, accounting for approximately 47.05% of the variations observed. Therefore, it is crucial to precisely control and take into consideration the amount of Zn added to achieve the desired hardness value in the material.…”
Section: Effect Of the Heat Treatments On Microhardness Of Al 7075-sc...mentioning
confidence: 87%
“…Table 1 illustrates that Al 7075-Sc contains 0.11% Sc in addition to 6.6% Zn, which is almost 1 percent higher than Al 7075 which has 5.62% Zn. The results of the study by Pruthvi and Shenoy [25] also indicated that the weight percentage of Zn has the most significant contribution to hardness, accounting for approximately 47.05% of the variations observed. Therefore, it is crucial to precisely control and take into consideration the amount of Zn added to achieve the desired hardness value in the material.…”
Section: Effect Of the Heat Treatments On Microhardness Of Al 7075-sc...mentioning
confidence: 87%